2022
DOI: 10.3390/foods11152361
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Function of Plant-Derived Bioactive Peptides: A Review

Abstract: Inflammation is considered to be a crucial factor in the development of chronic diseases, eight of which were listed among the top ten causes of death worldwide in the World Health Organization’s World Health Statistics 2019. Moreover, traditional drugs for inflammation are often linked to undesirable side effects. As gentler alternatives to traditional anti-inflammatory drugs, plant-derived bioactive peptides have been shown to be effective interventions against various chronic diseases, including Alzheimer’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 82 publications
0
27
0
Order By: Relevance
“…Studies have proven the safety of CPs. They also have various functions, such as antioxidant, anti-inflammatory, anti-hypertensive, immune boosting, and anti-fatigue [ 4 , 17 ]. Some researchers have found a protective effect of CPs against early alcoholic liver injury in mice and rats [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have proven the safety of CPs. They also have various functions, such as antioxidant, anti-inflammatory, anti-hypertensive, immune boosting, and anti-fatigue [ 4 , 17 ]. Some researchers have found a protective effect of CPs against early alcoholic liver injury in mice and rats [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ALD-protective ingredients extracted from plants and animals have attracted attention from researchers in academia and industry. Numerous studies have confirmed that food-derived oligopeptides can be used as potential dietary therapeutics and new functional raw materials for enhancing health [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation is how the body restores itself after injury, replaces damaged tissue and combats pathogens [ 195 ]. Inflammation may be acute or chronic.…”
Section: Biopeptides’ Potential In Cosmeceutical Applicationsmentioning
confidence: 99%
“…Low molecular weight peptides can reach their target place intact (they have few cleavage sites for endopeptidase enzymes) and have specific transport modes. Peptide transport modes include PepT1 transporters, cytokinesis, cellular bypass, and passive diffusion; dipeptides and tripeptides can also be in the PepT1 category [ 195 ]. Regardless of amino acid composition, highly hydrophobic biopeptides containing leucine, tryptophan, and phenylalanine have anti-inflammatory potential.…”
Section: Biopeptides’ Potential In Cosmeceutical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation